2010
DOI: 10.1016/j.vaccine.2010.05.062
|View full text |Cite
|
Sign up to set email alerts
|

The potential value of Clostridium difficile vaccine: An economic computer simulation model

Abstract: Efforts are currently underway to develop a vaccine against Clostridium difficile infection (CDI). We developed two decision analytic Monte Carlo computer simulation models: (1) an Initial Prevention Model depicting the decision whether to administer C. difficile vaccine to patients at-risk for CDI and (2) a Recurrence Prevention Model depicting the decision whether to administer C. difficile vaccine to prevent CDI recurrence. Our results suggest that a C. difficile vaccine could be cost-effective over a wide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 48 publications
1
28
0
Order By: Relevance
“…10,11 A recent computer simulation shows that vaccination could be the cost-effective approach in the prevention and treatment of CDI, especially the recurrent CDI. 12 It was initially reported that anti-TcdA antibodies were sufficient to protect the host against CDI. 13,14 However, recent studies demonstrated an even more important role of TcdB in the pathogenesis of CDI, [15][16][17][18] suggesting that an effective vaccine should target both toxins.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 A recent computer simulation shows that vaccination could be the cost-effective approach in the prevention and treatment of CDI, especially the recurrent CDI. 12 It was initially reported that anti-TcdA antibodies were sufficient to protect the host against CDI. 13,14 However, recent studies demonstrated an even more important role of TcdB in the pathogenesis of CDI, [15][16][17][18] suggesting that an effective vaccine should target both toxins.…”
Section: Introductionmentioning
confidence: 99%
“…TcdB appears to be better evolved to catalyze the more long-lasting inflammatory events in the disease process by killing human gut and immune cells and eliciting or subverting local inflammatory responses by causing the local production of interleukin 1␤ (IL-1␤), tumor necrosis factor alpha (TNF-␣), IL-6, and IL-8 and being involved in systemic disease in a piglet model (21)(22)(23) Neutralizing and protective antibodies against TcdA and TcdB have been generated by both active and passive vaccination of animals (24,25). Vaccination offers the potential advantage of generating a polyclonal response, but the disadvantages relate to the timing of vaccine administration relative to the perceived risk of infection and variability in the strength and speed of a patient's immune response (26)(27)(28)(29). Parenteral administration of purified antibodies offers control over both timing and dose.…”
mentioning
confidence: 99%
“…A previous model of CDI vaccination demonstrated cost-effectiveness even with wide-ranging risks of CDI and varied vaccine efficacies and costs. 44 A CDI vaccine is therefore an appealing goal, with the potential for substantial clinical impact in healthcare institutions across the world.…”
Section: Active C Difficile Immunisationmentioning
confidence: 99%